The role of habit in physical activity maintenance: Evidence from the LifelongU intervention - Dandan Huang; Shahabuddin Bin Hashim; Haopeng Zhang; Yang Xinggang; Nuannuan Deng (Environment and Social Psychology, 2025)
The prevalence of physical inactivity is rising in the world and is associated with noncommunicable diseases and mental health problems. While behaviour change interventions that promote physical activity initiation have been relatively successful, lapses and relapses are frequent in these interventions. This study aims to develop and test an integrative intervention to promote physical activity habits among physically inactive university students. 36 individuals were enrolled and assigned to one of two arms. The experimental group received a 12-week LifelongU intervention, while the control group participated in a regular physical education course. Linear mixed-effects models revealed significant changes in habit over time, with a significant group × time interaction indicating that habit development trajectories differed between the experimental and control groups. Similarly, physical activity showed a significant group × time interaction, indicating more favourable and sustained trajectories in the intervention group across the study period. Together, these findings suggest that habit development may play an important role in supporting PA maintenance over time. Key active components of the LifelongU intervention included (a) the use of a running application for self-monitoring, (b) achievable goal-setting, and (c) habit formation behaviour change techniques. Future studies using randomized designs, larger samples, and objective physical activity measures are needed to confirm and extend the present results.